Neutrophil gelatinase associated lipocalin-2 (Ngal) levels in preeclampsia - H. Yolli; M.E. Demir; R. Yildizhan (IMR Press, 2020)
Objectives: Lipocalin-2 (LCN-2) is an immune modulator. It is highly associated with inflammation, ischemia, neoplastic invasion, and transformation. Preeclampsia (PE) is a pregnancy-related disease resulting from the incomplete invasion of trophoblasts. Endothelial cytokines and inflammation have crucial roles in the pathogenesis of PE. We aimed to investigate serum LCN-2 levels in pregnant women with either no PE, mild PE or severe PE. Furthermore, we determined how LCN-2 levels relate to findings of Doppler ultrasound of the arteries in these patients. Material and Methods: Pregnant women with severe PE (n = 51), mild PE (n = 27), or no PE (n = 42) were involved in the study. Serum LCN-2 levels and Doppler ultrasonography (USG) evaluation were performed at the time of diagnosis of PE or in the cases of uncomplicated pregnancy, just prior to delivery. Women with non-complicated pregnancies were followed up for an additional 8 weeks after delivery. Intrauterine growth restriction (IUGR) was evaluated according to Alexander curve references. Results: Serum LCN-2 levels were significantly higher in pregnant women with PE. Higher LCN-2 levels were found in association with abnormal uterine blood flow and IUGR. Mean gestational age was lower in preeclamptic pregnancies and associated with high serum levels of LCN-2. Conclusion: PE is one of the most prevalent causes of pregnancy-associated complications. Early diagnosis and management of the disease are crucial. The level of serum LCN-2 may provide additional prognostic value along with other clinical and laboratory features of the disease.